Fetal and Neonatal Outcomes in Women Reporting Ingestion of Licorice (Glycyrrhiza uralensis) during Pregnancy - Choi, June-Seek; Han, Jung-Yeol; Ahn, Hyun-Kyong; Ryu, Hyun-Mee; Kim, Moon-Young; Chung, Jin-Hoon; Nava-Ocampo, Alejandro A.; Koren, Gideon (Planta Medica, 2013)
Maternal intake of licorice from dietary sources has been associated with adverse maternal and fetal outcomes. We prospectively studied the outcome of 185 singleton pregnancies who took over-the-counter or naturopathic formulations containing licorice during their pregnancy, and 370 age-matched singleton pregnant controls that were not exposed to any potential teratogen. The indication in 56.8 % of the women taking licorice was for cough and cold control, with the maximum dose of 2104 mg/day and exposure occurring between the 4th day and 25th week of gestation. The rate of stillbirths was marginally higher among women who took licorice than those who did not (OR = 7.9; 95 % CI 0.9–71.5; p = 0.048), and significantly higher when compared to the general population in the Republic of Korea (OR = 13.3; 95 % CI 4.9–35.8; p < 0.001). Other fetal outcomes assessed in the study were similar between the two study groups, e.g., the OR of major malformations was 3.9 (95 % CI 0.4–43.5; p = 0.27). In conclusion, the present study suggests that licorice is not a major teratogen. However, whether licorice may increase the risk of stillbirths requires careful consideration in further studies with a larger sample size.
Keywords: Glycyrrhiza uralensis; Leguminosae; licorice; natural products; plant extracts; pregnancy outcomes